Climate Variability and Water Resources in the Souss-Massa Region: A Study of Rainfall Patterns - Jawad EL HAWARI; Youness BOUHAFA; Abd Ellatif SINBRI; Mohamed EL GHACHI (African Journal of Advanced Pure and Applied Sciences, 2023)
This study focuses on the climatic characteristics of the Souss-Massa watershed, specifically analyzing precipitation and temperature patterns. The findings reveal that the region experiences an arid to semi-arid climate with an oceanic influence near the coast. Variability in rainfall is observed across different seasons, with winter receiving the highest amount of precipitation, followed by autumn and spring. In contrast, summer is the driest season, contributing minimally to the total rainfall. Spatially, the coastal and upstream areas receive more rainfall compared to the downstream areas, with notable variations between the north and south of the watershed. The study emphasizes the importance of understanding the spatiotemporal distribution of rainfall for better water resource management in the region. Overall, the Souss-Massa watershed exhibits both temporal and spatial irregularities in temperature and precipitation, characterized by alternating wet and dry years.